Caries diagnosis in dental practices: Results from dentists in a Brazilian community - Da Silva Tagliaferro, Elaine Pereira [UNESP]; Valsecki, Aylton [UNESP]; Rosell, Fernanda Lopez [UNESP]; Correa da Silva, Silvio Rocha [UNESP]; Riley, Joseph L.; Gilbert, Gregg H.; Gordan, Valeria Veiga (Operative Dentistry, 2019)
The aim of this study was to assess practices related to diagnosis of dental caries among dentists (n=217) from Araraquara, São Paulo State, Brazil. Data on sociodemographic information and practitioner characteristics were collected using a pretested questionnaire, and data on practices related to caries diagnosis were gathered by using a translated and culturally adapted questionnaire from the US National Dental Practice-Based Research Network. Descriptive statistics and regression analyses were used for data analysis. Respondents reported using in most of their patients radiographs (Rx) to diagnose proximal caries (59%), explorer (Ex) for the diagnosis of occlusal caries (64%) and on the margins of existing restorations (79%), as well as air jet (AJ) with drying (92%). Magnification (M) (25%), fiber optic transillumination (FOTI; 14%), and laser fluorescence (LF) (3%) were used in the minority of patients. Regression analysis revealed that the following dentists’ characteristics were significantly associated (p,0.05) with the use of diagnostic methods on a greater percentage of their patients: advanced degree (Rx, FOTI), higher percentage of patients with individu-